2020
DOI: 10.1155/2020/3198689
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral Avulsion during Semirigid Ureteroscopy: A Single-Centre Experience

Abstract: Aims. The aim of the study is to present our experience with the management of ureteral avulsions following semirigid ureteroscopy for ureteral stones. This is one of the largest series reported so far. Methods and Materials. It is a retrospective and observational study done at Sri Ramachandra Institute of Higher Education and Research over the last 18 years. Results. There were seven cases of ureteral avulsion following semirigid ureteroscopy. All patients were males with a mean age of 35.7 years. All had im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In addition, large impacted stones at this location lead to the formation of a weak or unhealthy ureter, causing avulsion to develop more easily in the proximal ureter where muscle support is weak, and the absence of little or no remaining ureter further reduces the success of end-to-end anastomosis. [ 2 , 10 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, large impacted stones at this location lead to the formation of a weak or unhealthy ureter, causing avulsion to develop more easily in the proximal ureter where muscle support is weak, and the absence of little or no remaining ureter further reduces the success of end-to-end anastomosis. [ 2 , 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…The repair of ureteral avulsions should preferably be undertaken immediately in stable cases because delayed repair may result in the loss of ureteral length due to fibrosis. [ 2 ] However, considering surgical experience, hospital conditions, or general state of the patient, s/he can be referred to a more experienced higher center after providing proper urinary drainage and discussing this option with the patient. [ 13 ] While delayed repair is recommended after approximately four to 8 weeks in experienced clinics, it has also been suggested that repair performed within the week of injury may cause fewer complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations